2018
DOI: 10.3390/su10103528
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Improving Transportation on Pilgrim Travel Behavior: Evidence from the Lhasa, Tibet, China

Abstract: Effective travel demand management measures provide the opportunity to fully utilize limited transportation resources, especially in underdeveloped areas. It is increasingly recognized that the improvement in existing transportation infrastructure and the optimization of traffic demand management method would result in a complicated urban transportation system with multiple travel modes. This paper aims to investigate the relationship between transportation improvements (e.g., pedestrian flow, free bus for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…These services include the efforts or deeds offered by service providers to induce good impressions. By synthesizing the previous perspectives of various authors [21][22][23][24][25], we found that the most important services are related to food, accommodation, and transportation as well as the services pertinent to medical care and religious guidance. Food quality has been cited as an effective factor of tourist attraction and spiritual preservation among pilgrims heading to a Buddhist temple [26] as well as Christian pilgrims in the Holy Land [27].…”
Section: Spirituality and Hajj Servicesmentioning
confidence: 99%
“…These services include the efforts or deeds offered by service providers to induce good impressions. By synthesizing the previous perspectives of various authors [21][22][23][24][25], we found that the most important services are related to food, accommodation, and transportation as well as the services pertinent to medical care and religious guidance. Food quality has been cited as an effective factor of tourist attraction and spiritual preservation among pilgrims heading to a Buddhist temple [26] as well as Christian pilgrims in the Holy Land [27].…”
Section: Spirituality and Hajj Servicesmentioning
confidence: 99%
“…Their work provides an effective evaluation method for the current situation of travel inequality in underdeveloped small cities [19]. Cheng et al focused on the pilgrims in Lhasa and measured the impact of their travel behavior using the multiple logit model [20]. Mayaud et al showed that at the same accessibility level, different groups depend on public transport differently [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These regulations together with the geographical conditions (e.g. being surrounded by mountains and its high altitude) and poor accessibility (Cheng et al, 2018) limit to a large extent the number of international tourists to Lhasa, and this is reflected in its relative low PDI value. Meanwhile, in addition to the common procedures applicable for foreign companies who want to enter the Chinese market, international tourism firms planning to operate in Tibet need to pass through two additional procedures, i.e.…”
Section: Lower Left Quadrantmentioning
confidence: 99%